PENGARUH PERILAKU KONSUMEN DAN BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KOPI KELILING DI JAWA TIMUR (The Influence of Consumer Behavior and Marketing Mix on The Purchase Decisions of Mobile Coffee Consumers in East Java) - Maulida, Dwi Laila; Leilasariyanti, Yennyka; Hariputra, Akbar; Ramadhani, Mirza (Jurnal Ilmiah Sosio Agribis, 2025)
Surabaya is one of the metropolitan cities with a highly active population, including both workers and students. Most of them enjoy coffee and embrace the growing coffee-drinking culture. However, due to their busy schedules, they prefer coffee that is convenient and can be taken on the go. This opportunity has led to the emergence of mobile coffee cart vendors scattered around main roads, especially near university campuses. The trend of mobile coffee is popular among young people due to its affordable price and decent taste. However, product development strategies are needed to ensure the sustainability and growth of current mobile coffee businesses. The purpose of this study is to analyze the influence of consumer behavior and marketing mix on consumers' purchasing decisions of mobile coffee in order to design effective and efficient strategies. The research method used is a quantitative approach utilizing SEM-PLS and IPA analyses. The results indicate that psychological factors and the marketing mix simultaneously and partially have a significant influence on purchasing decisions for mobile coffee in Surabaya. Meanwhile, the IPA analysis shows that the product variety indicator falls into quadrant 4, meaning that this indicator needs to be evaluated.Keywords: Mobile Coffee, Consumer Behavior, Marketing Mix, SEM-PLS.